Cell division- and DNA replication-free reprogramming of somatic nuclei for embryonic transcription - Junko Tomikawa (Elsevier, 2021)
Summary: Nuclear transfer systems represent the efficient means to reprogram a cell and in theory provide a basis for investigating the development of endangered species. However, conventional nuclear transfer using oocytes of laboratory animals does not allow reprogramming of cross-species nuclei owing to defects in cell divisions and activation of embryonic genes. Here, we show that somatic nuclei transferred into mouse four-cell embryos arrested at the G2/M phase undergo reprogramming toward the embryonic state. Remarkably, genome-wide transcriptional reprogramming is induced within a day, and ZFP281 is important for this replication-free reprogramming. This system further enables transcriptional reprogramming of cells from Oryx dammah, now extinct in the wild. Thus, our findings indicate that arrested mouse embryos are competent to induce intra- and cross-species reprogramming. The direct induction of embryonic transcripts from diverse genomes paves a unique approach for identifying mechanisms of transcriptional reprogramming and genome activation from a diverse range of species.